Descemet Membrane Endothelial Keratoplasty in an Eye with Fuchs Endothelial Dystrophy and Keratoconus. Issue 1 (2017) - Cooper, Elizabeth; Parker, Jack S.; Parker, John S.; Melles, Gerrit R.J.
Purpose: To report a case of Descemet membrane endothelial keratoplasty (DMEK) performed with phacoemulsification and intraocular lens implantation (triple procedure) for coexisting keratoconus (KC), Fuchs endothelial dystrophy (FED), and visually significant cataract. Case description: One eye of one patient with moderate and stable KC, FED, and visually significant cataract was treated with combined DMEK and phacoemulsification with intraocular lens implantation (triple procedure). Visual acuity and corneal reflectivity/densitometry, thickness, and topographic measurements were recorded and compared to their preoperative values. At all postoperative time points, the endothelial graft was found to be completely attached. By 3 months postoperatively, the patient's best spectacle corrected vision had improved from 20/50 (0.4) to 20/25 (0.8) where it remained stable. No intra- or postoperative complications were experienced. Conclusions: DMEK may be an effective alternative to penetrating keratoplasty in eyes with coexisting stable KC and FED.